Konstanzer Seminar on Monetary Theory and Monetary Policy 1970 - Manfred J. M. Neumann (Kredit und Kapital, 1971)
Constance Seminar on Monetary Theory and Monetary Policy 1970 This is a report on an international symposium on monetary theory, the hosts of which were Karl Brunner and the team of the monetary theory and monetary policy research project in the Economic Sciences Department of the University of Constance. The basic idea of the future annual Constance Seminars on Monetary Theory and Monetary Policy is to induce the monetary theory debate in Germany and other European countries to emerge from its restricted national ambit and to intensify the direct dialogue among European and American monetary theorists and members of monetary policy agencies. At the same time, it is intended to stimulate interest in the study of European monetary processes. At the 1970 conference nine papers were read, the contents of which are outlined this report. One notable aspect is that the proceedings were concentrated on two main themes; on the one hand the theoretical conception of monetarism and its consequences for monetary policy (papers by L. C. Andersen, K. Brunner er A. H. Melzer), and on the other the analysıs of German monetary policy (papers by H. Irmler, M. J. M. Neumann, J. Siebke, M. Willms)
Keywords: 330